Cubozoan Sting-Site Seawater Rinse, Scraping, and Ice Can Increase Venom Load: Upending Current First Aid Recommendations - Angel Anne Yanagihara (Toxins, 2017)
Cnidarian envenomations are the leading cause of severe and lethal human sting injuries from marine life. The total amount of venom discharged into sting-site tissues, sometimes referred to as “venom load”, has been previously shown to correlate with tentacle contact length and sequelae severity. Since <1% of cnidae discharge upon initial tentacle contact, effective and safe removal of adherent tentacles is of paramount importance in the management of life-threatening cubozoan stings. We evaluated whether common rinse solutions or scraping increased venom load as measured in a direct functional assay of venom activity (hemolysis). Scraping significantly increased hemolysis by increasing cnidae discharge. For Alatina alata, increases did not occur if the tentacles were first doused with vinegar or if heat was applied. However, in Chironex fleckeri, vinegar dousing and heat treatment were less effective, and the best outcomes occurred with the use of venom-inhibiting technologies (Sting No More® products). Seawater rinsing, considered a “no-harm” alternative, significantly increased venom load. The application of ice severely exacerbated A. alata stings, but had a less pronounced effect on C. fleckeri stings, while heat application markedly reduced hemolysis for both species. Our results do not support scraping or seawater rinsing to remove adherent tentacles.